2010
DOI: 10.1038/oby.2009.364
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Metabolically Healthy but Obese Individuals in Sedentary Postmenopausal Women

Abstract: IntroductIonObesity is widely recognized as an important risk factor for the development of metabolic complications such as insulin resistance, hypertension, and dyslipidemia, which may increase the risk of cardiovascular diseases and type 2 diabetes (1-3). However, the presence of these obesity-related metabolic disturbances varies widely among obese individuals (4-8). Accordingly, a unique subset of obese individuals has been described in the medical literature that appears to be protected or more resistant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
110
3
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(124 citation statements)
references
References 36 publications
6
110
3
5
Order By: Relevance
“…Again, our findings are partly in agreement with the literature (Koster et al, 2010) and may be related to differing body fat content according to the definition of MHO used (Messier et al, 2010). Still, the differences in TNF-a levels among some MHO definitions remained significant after adjusting for waist or body fat percentage ( Table 6), suggesting that metabolic pathways other than differing fat content might intervene.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Again, our findings are partly in agreement with the literature (Koster et al, 2010) and may be related to differing body fat content according to the definition of MHO used (Messier et al, 2010). Still, the differences in TNF-a levels among some MHO definitions remained significant after adjusting for waist or body fat percentage ( Table 6), suggesting that metabolic pathways other than differing fat content might intervene.…”
Section: Discussionsupporting
confidence: 82%
“…Conversely, the MHO definition of Meigs includes many components (waist, systolic blood pressure, diastolic blood pressure), which are significantly associated with inflammatory markers, thus, explaining the differences between MHO and non-MHO subjects. Overall, our findings suggest that the lower levels of inflammatory biomarkers found among MHO subjects could be due to a lower or different fat mass distribution (higher subcutaneous and lower visceral; Messier et al, 2010), a different genetic background or simply a selection bias (criteria used to define MHO). Nevertheless, further studies are needed to assess which of these hypotheses (and possibly others) are actually true.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Our findings suggest that the prevalence of MHO varies considerably according to the obesity markers and the criteria used to define metabolic abnormalities, thus raising the question of which criteria and obesity markers to use, and the comparability between studies. Furthermore, o5% of all obese subjects (irrespective of the anthropometric marker used to define obesity) were considered as MHO by all six definitions used, a finding also reported in another study, where no MHO subject was identified within the five methods used (Messier et al, 2009 Using BMI to define obesity, the prevalence of MHO was lower than reported in other studies (Figure 3). An exception was the prevalence of MHO in women defined by the criteria of Karelis et al (2004), which showed a good agreement with the previously published data.…”
Section: Discussioncontrasting
confidence: 51%
“…Metabolic abnormalities were defined using different criteria (see Table 1 for details). Prevalence of metabolically healthy obesity S Velho et al (Messier et al, 2009), still our data suggest that an increased waist is negatively related with MHO among BMI-defined obese subjects. Nevertheless, the wide range of MHO prevalence according to the set of criteria used observed in this study stresses the need for an expert consensus to standardize the identification of MHO subjects, as suggested previously (Messier et al, 2009).…”
Section: Discussionmentioning
confidence: 51%